DEVELOPMENT AND CHARACTERIZATION OF SUSTAINED RELEASE METHOTREXATE LOADED CUBOSOMES FOR TOPICAL DELIVERY IN RHEUMATOID ARTHRITIS - KAPOOR, KARISHMA; PANDIT, VINAY; NAGAICH, UPENDRA (International Journal of Applied Pharmaceutics, 2020)
Objective: Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are essential part of the administration of Rheumatoid Arthritis (RA). Methotrexate (MTX) is effective for tumor necrosis factor alpha (TNF-a) biologic agents, indicated only in minority of patients suffering from severe RA. MTX remains the "anchor drug" in the treatment of RA. For delivery improvement, novel pharmaceutical drug delivery system i.e. MTX-Cubosomes were developed. Methods: Poloxamer 407 and Glycerol monooleate (Monoelin, MO) used and the formulation were characterized as a sustained release drug delivery system for Methotrexate. Different ratios of Monolein, Poloxamer 407 and water were used to develop the different cubosomes using homogenization and emulsification method. Characterization of formulations for morphology was performed and also particle size distribution by Transmission Electron Microscopy (TEM). Results: Formulation showed the internal cubic structures of the vesicles. The particle size of the formulations was found to be ranging from 53.21 to 185.32 nm, zeta potential of the formulations varied from-18.20-36.10 mV. The cubosomal formulation exhibited good entrapment efficiency along with high drug loading. Compatibility with the excipients was also established. An in vitro release study was done using Franz Diffusion cell indicated sustained release of the formulation at a rate of 1.25 %/h. Cubosomes proved to be reliable system for sustained transdermal drug delivery system. Conclusion: Methotrexate cubosomes is a novel medication delivery framework and in this examination it has been developed and characterized. The formulations were found to be promising in terms of its characterization parameters like particle size, zeta potential, entrapment efficiency, loading capacity, release kinetics, and stability, suitable for topical delivery.